2000
DOI: 10.1046/j.1365-2044.2000.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain control following remifentanil‐based anaesthesia for major abdominal surgery

Abstract: SummaryEighty patients undergoing major abdominal surgery using remifentanil-based anaesthesia were randomly allocated in a double-blind manner to receive an intravenous bolus of fentanyl, buprenorphine, morphine or piritramide 20 min before the end of surgery. A reduced dose was administered postoperatively when patients reported moderate pain. Subsequent analgesia was provided by patient-controlled analgesia (PCA). The mean time from the end of anaesthesia to spontaneous respiration was 9 6 5 min. At ®rst pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 17 publications
0
11
0
4
Order By: Relevance
“…O rápido final de ação torna necessária a utilização de outros analgésicos antes de se interromper a infusão do remifentanil. Para cirurgias torácicas, abdominais ou ortopédicas o uso de antiinflamatórios é insuficiente para garantir um despertar sem dor, o que torna necessária a administração conjunta, por via venosa, de opióide de ação mais prolongada como o fentanil (até 150 µg) ou morfina (até 0,15 mg.kg -1 ), a utilização de bloqueios regionais ou a infiltração local de anestésico antes do final da cirurgia 43,44 . Quando a morfina é utilizada para colecistectomia, sua administração é mais eficaz quando feita na indução, junto com o início da infusão de remifentanil, devido ao seu prolongado tempo de latência 45 .…”
Section: Analgesia De Transiçãounclassified
See 1 more Smart Citation
“…O rápido final de ação torna necessária a utilização de outros analgésicos antes de se interromper a infusão do remifentanil. Para cirurgias torácicas, abdominais ou ortopédicas o uso de antiinflamatórios é insuficiente para garantir um despertar sem dor, o que torna necessária a administração conjunta, por via venosa, de opióide de ação mais prolongada como o fentanil (até 150 µg) ou morfina (até 0,15 mg.kg -1 ), a utilização de bloqueios regionais ou a infiltração local de anestésico antes do final da cirurgia 43,44 . Quando a morfina é utilizada para colecistectomia, sua administração é mais eficaz quando feita na indução, junto com o início da infusão de remifentanil, devido ao seu prolongado tempo de latência 45 .…”
Section: Analgesia De Transiçãounclassified
“…Fast remifentanil recovery requires other analgesics before its withdrawal. For chest, abdominal or orthopedic surgeries anti-inflammatory drugs are unable to assure painless emergence and require the association of intravenous opioids of more prolonged action, such as fentanyl (up to 150 µg) or morphine (up to 0.15 mg.kg -1 ), of regional blocks or of local anesthetic infiltration before surgery completion 43,44 . When morphine is used for cholecystectomy it is more effective if administered during induction, together with remifentanil, due to its prolonged onset time 45 .…”
Section: Transitional Analgesiamentioning
confidence: 99%
“…These interesting properties allow infusion of high doses during a short time period without compromising a predictable and rapid recovery. 44,47 However, recent human studies have demonstrated difficult postoperative pain management [52][53][54][55] and remifentanil was described to potentiate NMDA recep- tor activity via -opioid receptors 56 leading to hyperalgesia. [57][58][59] Thus, if this was the type of tolerance or resistance involved in the intraoperative response to surgical stimulation in our patients, then the improved analgesia of the xenon group can be explained by an interaction of xenon with NMDA receptors that could have been activated by either or both of the perioperative nociceptive inputs and by the administration of opioids.…”
Section: The Effect Of Nmda Receptors On Pain Perceptionmentioning
confidence: 99%
“…Denn wegen des raschen Wirkungsverlustes muss nach Remifentanil gestützten Narkosen die postoperative Behandlung von Schmerzen neu gelöst werden [31]; ein Problem, dass kaum einer a priori in Betracht gezogen hat. Viele der Lösungsvorschläge beruhen auf dem zusätzlichen Einsatz länger wirkender Opioide [32,33] oder auf der zusätzlicher Anlage einer Regionalanalgesie [34]. Obwohl beide Verfahren gut funktionieren, erhöht sich der Aufwand für eine "Remifentanil-Narkose" und die Vorteile der guten Steuerbarkeit relativieren sich.…”
Section: 5unclassified